2017
DOI: 10.14233/ajchem.2017.20657
|View full text |Cite
|
Sign up to set email alerts
|

in vitro Antioxidant Activity and Total Phenolic Content of Rhizome Extracts from Acorus calamus Linn.

Abstract: The present study describes antioxidant activities of methanolic extracts from Acorus calamus (Araceae) rhizomes. The antioxidant potential of methanolic extracts were determined by in vitro antioxidant screening models viz. DPPH radical scavenging activity, reductive ability and metal chelating activity along with the estimation of total phenolics, flavonoids and ortho-dihydroxy contents. The total phenolic, flavonoid and ortho-dihydroxy contents estimated ranged from 1.67 ± 0.288 to10.42 ± 0.180 mg/g gallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Phenolic compounds have great importance in free radicals scavenging potential. Researchers found that the role of flavonoids, alkaloids and other phenolic compounds in scavenging the free radicals and the antioxidant potential [39].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds have great importance in free radicals scavenging potential. Researchers found that the role of flavonoids, alkaloids and other phenolic compounds in scavenging the free radicals and the antioxidant potential [39].…”
Section: Discussionmentioning
confidence: 99%
“…The natural products from Marsilea minuta [ 108 ], rhizome extract of Acorus calamus [ 149 ], and petroleum-ether extract of root parts of Hygrophila schulli [ 95 ] showed promising sedative activity. Bacopa monnieri and Enhydra fluctuans plant species have potential sedative actions [ 156 , 157 ].…”
Section: Uses Of Aquatic and Semiaquatic Medicinal Plantsmentioning
confidence: 99%
“…The flour of fruits of Trapa bispinosa is reported to have important commercial uses in the milk industry and as a filler in the pharmaceutical industry [ 169 ]. Similarly, the rhizome extract and essential oils of the Acorus calamus are widely used in the flavoring industry and for commercial purposes [ 149 , 175 ].…”
Section: Uses Of Aquatic and Semiaquatic Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As volatile fragrance oil, it is used in killing pests and bacteria. Some previous reports showed the antibacterial, and antifungal activity along with antioxidant activity by the EO and extract of the plant from different foreign countries, however, not much detailed research has been done on the A. calamus found in Nepal [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%